How Do Learning Models and Media Affect Students' Science Literacy?: A Review - Selaras, Ganda Hijrah (Bioeducation Journal, 2025)
Science literacy is a critical competency in the 21st century, equipping students with the skills to understand, evaluate, and apply scientific concepts in real-world contexts. This review examines the impact of various learning models and media on improving students’ science literacy. The study synthesizes findings from recent research to explore how instructional approaches such as Project-Based Learning (PjBL), Inquiry-Based Learning (IBL), and Blended Learning promote students’ ability to think critically and solve scientific problems. In addition, the role of digital and traditional media, including virtual simulations, e-modules, and hands-on laboratory activities, is discussed in promoting engagement and conceptual understanding. Key factors influencing the effectiveness of learning models and media are also analyzed. The review highlights gaps in current studies and identifies best practices for implementing learning strategies that support science literacy. This article aims to provide evidence-based insights to educators, researchers, and policymakers to design effective instructional strategies that foster scientifically literate individuals.